2010
DOI: 10.4049/jimmunol.1001635
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation of 3-Methylcholanthrene–Induced Fibrosarcoma Determines Antitumor Immune Responses during Immunoediting

Abstract: Sialylation of tumor cells is involved in various aspects of their malignancy (proliferation, motility, invasion, and metastasis); however, its effect on the process of immunoediting that affects tumor cell immunogenicity has not been studied. We have shown that in mice with impaired immunoediting, such as in IL-1α−/− and IFNγ−/− mice, 3-methylcholanthrene–induced fibrosarcoma cells are immunogenic and concomitantly bear low levels of surface sialylation, whereas tumor cells derived from wild type mice are non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…56 Interestingly, a2-6 sialylation also showed significant effects on cancer immunoediting, a process in which cell death plays a critical role. 57 An interesting example of how lectin-receptor interactions control inflammatory response has been shown for galectin-8. Binding of galectin-8 to CD44 activates the proapoptotic machinery in joint inflammatory cells and promotes relief of inflammation.…”
Section: Galectin Counter-receptors In the Initiation Of Cell Deathmentioning
confidence: 99%
“…56 Interestingly, a2-6 sialylation also showed significant effects on cancer immunoediting, a process in which cell death plays a critical role. 57 An interesting example of how lectin-receptor interactions control inflammatory response has been shown for galectin-8. Binding of galectin-8 to CD44 activates the proapoptotic machinery in joint inflammatory cells and promotes relief of inflammation.…”
Section: Galectin Counter-receptors In the Initiation Of Cell Deathmentioning
confidence: 99%
“…Distinctly glycosylated tumor antigens on the cell surface or on secreted molecules (e.g., mucins) are diagnostically exploited as tumor markers (e.g., CA125, MUC1, CEA, and CA19-9). Sialoglycans influence many critical steps in tumor biology, including immunoediting, tumor growth and proliferation, invasion, metastasis, and angiogenesis; in some instances, their presence has been correlated with poor patient survival (1,2,(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Another line of evidence indicating the importance of sialylation in tumor immunology is a recent study in the methylcholanthrene induced fibrosarcoma model (199,200). It was observed that methylcholanthrene induced fibrosarcomas grown in immunecompetent mice expressed high levels of sialic acid on their cell surface.…”
Section: Sialylated N-linked or O-linked Glycans-sialylation Of Glycomentioning
confidence: 99%
“…It was observed that methylcholanthrene induced fibrosarcomas grown in immunecompetent mice expressed high levels of sialic acid on their cell surface. However, the same type of tumors grown in IL-1alpha −/− and IFN-γ −/− immunocompromised mice expressed lower levels of sialylation (199). Extensive analysis in this model resulted in the understanding that the immune cells were selectively lysing fibrosarcoma cells that were expressing low levels of sialic acids while those expressing high levels of sialic acid were being selectively excluded from immune cell attack.…”
Section: Sialylated N-linked or O-linked Glycans-sialylation Of Glycomentioning
confidence: 99%